The role of pollution prevention strategies, best management practices and cleaner production in hospital wastewater management - Dissanayake, Priyanka (2009)
Hospital effluents can be especially hazardous and toxic due to their content of chemical, pathogenic and bio-hazardous wastes. Many of these toxic pollutants are not fully removed or neutralized by traditional municipal wastewater treatment plants, which are primarily designed to address parameters such as Biochemical Oxygen Demand (BOD), Total Suspended Solids (TSS), etc. They are also not easily removed by filtration, settling or flocculation. The common disposal of liquid waste from hospitals into the municipal network collection system or in cesspits is of serious concern and it requires swift and effective address. Wastewater from hospitals contains pollutants that are hazardous and require on-site management to prevent contaminating the city's sewage system and other surface waters. Unlike industrial operations that typically have a few large volume waste streams; hospitals generate different volumes of a wide variety of wastes and emissions. Most important chemicals in hospital wastewater are disinfectants (due to their major use in hospital practice), antibiotics, cytostatic agents, anesthetics, heavy metals (silver, chromium, zinc, lead, copper, platinum, and mercury), rare earth elements (gadolinium, indium, and osmium) and iodinated X-ray contrast media. Pollution prevention strategies and Best Management Practices (BMPs) to pollutant load reduction at the source is the best solution available to overcome this problem. The pollutant load reduction can be initiated by applying pollution prevention strategies and Best Management Practices (BMPs) to practices that use these chemicals. The goal of pollution prevention in healthcare environments is the same as throughout industry do to eliminate and/or reduce pollution at the source. The major difference when undertaking pollution prevention at healthcare facilities is that they do not manufacture a 'product', operate a fabrication 'process' or generate waste materials that can be readily recycled, reused or reprocessed. Therefore, the role of Pollution Prevention Strategies, Best Management Practices and Cleaner Production will be somewhat different than other industrial sectors. Pollution Prevention Strategies, Best Management Practices and Cleaner Production applicable to hospital wastewater management in Sri Lanka and Bangladesh are addressed in this paper.